2020
DOI: 10.1093/rheumatology/keaa093
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in spondyloarthritis: unravelling the complexities

Abstract: Tobacco smoking is a major threat to health. There is no doubt about the need to promote and support cessation at every opportunity. Smoking has a clear role in RA, but what evidence is there that the same relationship exists in SpA? In this review, we examine (the less cited) paradoxes and contradictions in the existing axial SpA (axSpA) and PsA literature; for example, smoking appears to be ‘protective’ for some axSpA manifestations. We also highlight findings from higher quality evidence: smoking is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…Chronic exposure to tobacco smoke through cigarette smoking is a serious public health problem that can lead to the development of serious diseases such as lung cancer, cardiovascular disease and chronic obstructive pulmonary disease (COPD) [ 24 , 25 ]. At the musculoskeletal level, there is consistent evidence that smoking is an important risk factor in the development of rheumatoid arthritis (RA), mainly in men, through its interaction with the citrullination process or with anti-citrullinated peptide antibodies (ACPAs) [ 26 , 27 ]. In the case of osteoporosis, smoking affects bone calcium homeostasis, and in osteoarthritis (OA), there is inflammation with a notable increase in oxidative stress [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to tobacco smoke through cigarette smoking is a serious public health problem that can lead to the development of serious diseases such as lung cancer, cardiovascular disease and chronic obstructive pulmonary disease (COPD) [ 24 , 25 ]. At the musculoskeletal level, there is consistent evidence that smoking is an important risk factor in the development of rheumatoid arthritis (RA), mainly in men, through its interaction with the citrullination process or with anti-citrullinated peptide antibodies (ACPAs) [ 26 , 27 ]. In the case of osteoporosis, smoking affects bone calcium homeostasis, and in osteoarthritis (OA), there is inflammation with a notable increase in oxidative stress [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al [88] also reported that smoking was associated with the risk of uveitis in Portuguese patients with spondyloarthropathies. Zhao et al [89] extensively reviewed the role of tobacco habits in spondylarthritis. Moreover, Zanón-Moreno et al [90] reported in chronic glaucoma that the IL-6, caspase-3, and PARP-1 levels were significantly higher in the plasma and aqueous humor of smoking elder women than in ex-smoking and non-smoking women of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the data so far suggests smoking may be associated with unfavourable patient reported outcomes, lower treatment adherence and response, but links with radiographic progression are inconclusive. Associations between smoking and disease severity may be underpinned by the inflammatory effects of smoking (Ambrose & Barua, 2004); CRP is ∼1.45 mg/dl higher in ever smokers versus never smokers, and 1.93 mg/dl higher in current versus non‐current smokers (Zhao et al., 2020). Furthermore, current smokers have active inflammation on MRI studies (Zhao et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, smoking is actually more prevalent in patients with AS compared to the general population, compounding the already elevated risk of CVD (Papagoras et al., 2014). In 2018, ∼15% of UK adults were classified as current smokers, but the prevalence in patients with AS ranges from 24% to 29% (Zhao et al., 2020), and may be a coping mechanism for pain and boredom (Aimer et al., 2015).…”
Section: Methodsmentioning
confidence: 99%